The impact of slip conditions on magnetohydrodynamics radiating fluid beyond an exponentially extended sheet - Mohamed Isa, Siti Suzilliana Putri; Md. Arifin, Norihan; Farooq, Umer (IOP Publishing, 2018)
A mathematical model is performed to analyse the magnetohydrodynamics (MHD) fluid flow and transmission of heat in the case of an exponentially extended sheet. The system is supressed by thermal radiation, which is constituted in the energy equation. The boundary contains velocity, thermal and mass slips. Similarity transformation is applied, to convert the governing equations (continuity, momentum, energy and mass diffusion equations) into ordinary differential equations (ODE). Then, the purpose of numerical shooting method is to perform the solutions in the ODE part. Finally, results are presented in the forms of table and graphs (skin friction coefficient, heat transfer rate, concentration gradient at the plate, and the profiles of velocity, temperature, concentration and concentration gradient) for various values of controlling parameters. The consequences of the controlling parameters on the system are described in details.